Agro-ecological zonation of Uttarakhand using geo-spatial techniques - BISHT, HIMANI; GAUTUM, SHWETA; PURANIK, HARSHVARDHAN; NAIN, A S (The Indian Journal of Agricultural Sciences, 2019)
In this study, the Agro-ecological zones (AEZs) of Uttarakhand were delineated based on land use/land cover, slope, soil texture, temperature and length of growing period (LGP) by using remote sensing and GIS. The Decision Tree Classifier (DTC) algorithm technique was used for delineation of Agro-ecological zones (AEZs). The land use/ land cover map was used as base map and slope map of entire state (other than snow bound region) having five classes (0-5°, 5-15°, 15-30°, 30-50° and >50°) was overlaid on soil texture map having three soil classes (frigid soils, loamy soils and sandy soils). Thereafter, temperature map with three thermal regimes (<0°C, 0-15°C, and >15°C) and length of growing period with two distinct classes (<120 days and >120 days) were overlaid on existing map. The small classes having number of pixel <1000 and the regions having temperature <0°C and slope of >50° were removed from the analysis because agriculture is not possible over these regions. Thereafter, the entire state of Uttarakhand was divided into 38 agro-ecological zones (AEZs).